2012
DOI: 10.1158/1078-0432.ccr-11-1049
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide Induces Apoptosis in Fludarabine-Resistant and Clinically Refractory CLL Cells

Abstract: Purpose: Environmental conditions in lymph node proliferation centers protect chronic lymphocytic leukemia (CLL) cells from apoptotic triggers. This situation can be mimicked by in vitro stimulation with CD40 ligand (CD40L) and interleukin 4 (IL-4). Our study investigates the impact of the drug leflunomide to overcome apoptosis resistance of CLL cells.Experimental Design: CLL cells were stimulated with CD40L and IL-4 and treated with fludarabine and the leflunomide metabolite A771726.Results: Resistance to flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 57 publications
3
37
0
Order By: Relevance
“…Previous studies have shown that leflunomide induced apoptosis in p53-defective CLL cells, suggesting a p53-independent mechanism of apoptosis induction by leflunomide [29], with similar results reported in multiple myeloma cells [25]. Our studies showed that leflunomide significantly induced apoptosis in neuroblastoma cells.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that leflunomide induced apoptosis in p53-defective CLL cells, suggesting a p53-independent mechanism of apoptosis induction by leflunomide [29], with similar results reported in multiple myeloma cells [25]. Our studies showed that leflunomide significantly induced apoptosis in neuroblastoma cells.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the inhibitors of DHODH are currently used for the therapy of autoimmune diseases, and celastrol has long been proved to be very effective for this kind of disease [40]. Furthermore, it was reported that the inhibition of DHODH could induce apoptosis [4143]. Teriflunomide, a well-known specific inhibitor of DHODH, could also induce significant apoptosis of APL cells in our study (Figure 6).…”
Section: Discussionsupporting
confidence: 61%
“…Mitochondrial respiration in hematopoietic and various other cell types is known to be affected by de novo pyrimidine synthesis in a Krebs cycle- and glucose-independent manner (38). Moreover, mTORC1 activation was recently shown to enhance glutamine flux through pyrimidine biosynthesis (1, 16) and leflunomide was reported to overcome Flu resistance in CLL (41). Consistent with those data, we found higher pCAD (S1859) levels in FluR cells.…”
Section: Discussionmentioning
confidence: 99%